Cut stroke in half: Polypill for primary prevention in stroke. Issue 6 (August 2018) - Brainin, Michael; Feigin, Valery; Martins, Sheila; Matz, Karl; Roy, Jayanta; Sandercock, Peter; Teuschl, Yvonne; Tuomilehto, Jaakko; Wiseman, Anita
This review summarizes the potential for polypill therapies for stroke prevention. While a number of studies applying different approaches regarding polypill have been performed, none of them has had a focus on stroke as the main outcome. A combination pill containing drugs such as statins, diuretics, and other antihypertensives is currently available in various formats. Estimates focusing mostly on primary prevention show that using such a combination drug a reduction in the 5-year stroke incidence by 50% can be achieved – especially in low- and middle-income countries with a high prevalence of risk factors even among people at young ages. A combination of a large supporting population-wide program with a registry-based quality control is the most likely perspective and can be achieved within a reasonable time frame and potentially have significant influence in young stroke populations.